Highly flexible and accurate serial picoinjection in droplets by combined pressure and flow rate control. Issue 18 (9th August 2022) - Breukers, Jolien; Op de Beeck, Hannah; Rutten, Iene; López Fernández, Montserrat; Eyckerman, Sven; Lammertyn, Jeroen
Abstract : This novel methodology to control serial picoinjectors allows for accurate and flexible combinatorial reagent addition into droplets. Abstract : Picoinjection is a robust method for reagent addition into microfluidic droplets and has enabled the implementation of numerous multistep droplet assays. Although serial picoinjectors allow to screen many conditions in one run by injecting different combinations of reagents, their use is limited because it is complex to accurately control each injector independently. Here, we present a novel method for flexible, individual picoinjector control that allows to inject a predefined range of volumes by controlling the flow rate of the injector as well as turning off injection by setting the equilibrium pressure, which resulted in a stable interface of the injector liquid with the main microfluidic channel. Robust setting of the equilibrium pressure of an injector was achieved by applying accurate ( R 2 > 0.94) linear models between the injector and oil pressure in real-time. To illustrate the flexibility of this method, we performed several proof-of-concepts using 1, 2 or 3 picoinjectors loaded with fluorescent dyes. We successfully demonstrated picoinjection approaches using time-invariant settings, in which an injector setting was applied for prolonged times, and time-variant picoinjection, in which the injector settings were continuously varied in order to sweep the injected volumes, both resulting in monodisperse (CV < 3.4%) droplet libraries with different but reproducible fluorescent intensities. To illustrate the potential of the technology for fast compound concentration screenings, we studied the effect of a concentration range of a detergent on single-cell lysis. We anticipate that this robust and versatile methodology will make the serial picoinjection technology more accessible to researchers, allowing its wide implementation in numerous life science applications.